KIMI.AR Application for Easier and Interactive Chemistry Learning - Irawan, Elysa Nensy; Salman, Fauzie; Putri, Aisyah Aira; Sakti, Rizky Hamdani; Mulya, Tri Seda; Venica, Liptia (Chemistry Education Department, 2023)
Chemistry is a crucial subject since it covers the structure and makeup of the world around us. However, chemistry is frequently cited as a subject that students dislike. Most secondary school pupils believe that chemistry is difficult, uninteresting, and unimportant. Therefore, an improvement in learning technic is needed. An application called KIMI.AR was created in this research. KIMI.AR is a learning media in the form of a mobile-based augmented reality application regarding elements and the formation of chemical reactions that are expected to solve high school students' problems in the chemistry learning process. What makes the KIMI.AR application better than other chemistry learning applications is the focus on the displayed material according to the user's level and displaying descriptions in addition to 3D visualization that students can access through their respective Android devices. So, through the KIMI.AR application, learning chemistry becomes easier and more interesting.